Epicardial Breakthrough Waves During Sinus Rhythm: Depiction of the Arrhythmogenic Substrate?. (September 2017) - Mouws, Elisabeth M.J.P.; Lanters, Eva A.H.; Teuwen, Christophe P.; van der Does, Lisette J.M.E.; Kik, Charles; Knops, Paul; Bekkers, Jos A.; Bogers, Ad J.J.C.; de Groot, Natasja M.S.
Abstract : Background: Epicardial breakthrough waves (EBW) during atrial fibrillation are important elements of the arrhythmogenic substrate and result from endo-epicardial asynchrony, which also occurs to some degree during sinus rhythm (SR). We examined the incidence and characteristics of EBW during SR and its possible value in the detection of the arrhythmogenic substrate associated with atrial fibrillation. Methods and Results: Intraoperative epicardial mapping (interelectrode distances 2 mm) of the right atrium, Bachmann's bundle, the left atrioventricular groove, and the pulmonary vein area was performed during SR in 381 patients (289 male, 67±10 years) with ischemic or valvular heart disease. EBW were referred to as sinus node breakthrough waves if they were the earliest right atrial activated site. A total of 218 EBW and 57 sinus node breakthrough waves were observed in 168 patients (44%). EBW mostly occurred at right atrium (N=105, 48%) and left atrioventricular groove (N=67, 31%), followed by Bachmann's bundle (N=27, 12%) and pulmonary vein area (N=19, 9%; P <0.001). EBW occurred most often in ischemic heart disease patients (N=114, 49%) compared with (ischemic and) valvular heart disease patients (N=26, 17%; P <0.001). EBW electrograms most often consisted of double and fractionated potentials (N=137, 63%). In case of single potentials, an R wave was observed in 88% (N=71) of EBW, as opposed to 21% of sinus node breakthrough waves (N=5; P <0.001). Fractionated EBW potentials were more often observed at the right atrium and Bachmann's bundle ( P <0.001). Conclusions: During SR, EBW are present in over a third of patients, particularly in thicker parts of the atrial wall. Features of SR EBW indicate that muscular connections between endo- and epicardium underlie EBW and that a slight degree of endo-epicardial asynchrony required for EBW to occur is already present in some areas during SR. Hence, an anatomic substrate is present, which may enhance the occurrence of EBW during atrial fibrillation, thereby promoting atrial fibrillation persistence.